Pathological Complete Response After Imatinib Mesylate Therapy in Inoperabl Gastrointestinal Stromal Tumor: A Case Report - Zengel, Baha; Alacacıoglu, Ahmet; Yagcı, Ayse; Postacı, Hakan; Kavak, Ozgur; Galip, Ali; Gokmen, Erhan (Fırat University, 2011)
Gastrointestinal stromal tumors are characterized by the expression of CD34 and c-kit (CD117) and represent the most common mesenchymal malignancy of the gastrointestinal tract. Imatinib mesylate is small molecule tyrosine kinase inhibitor that suppresses transmembrane receptor c-kit products. Clinical studies for metastatic and inoperabl GISTs have demonstrated partial response rate ranging from 40% to 69% in patients treated with imatinib mesylate. But complete response is rare. We present a 46 year old man patient with unresectable gastrointestinal stromal tumor that has histopatologically proven complete response to imatinib mesylate therapy.

Gastrointestinal stromal tümörler CD34 and c-kit (CD117) ekspresyonu ile karekterize olan, gastrointestinal sistemin en sık görülen mezenkimal maligniteleridir. İmatinib mesiat, transmembran reseptör c-kit ürünlerini baskılayan küçük molekül tirozin kinaz inhibitörüdür. Metastatik ve inoperabl gastarointestinal stromal tümörlerde yapılan klinik çalışmalarda imatinib mesilat tedavisi ile parsiyel yanıt oranları 40% ile 69% arasındadır. Fakat tam yanıt nadirdir. Bu yazımızda 46 yaşında anrezektabl gastrointestinal stromal tümorlü erkek hastada, imatinib mesilat tedavisi ile sağlanan patolojik tam yanıt değerlendirilmiştir.
Inoperabl Gastrointestinal Tümörde Imatinib Mesilat Tedavisi Sonrası Patolojik Tam Yanıt: Olgu Sunumu